2007
DOI: 10.1002/chem.200601900
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles in Organic Capsules: A Supramolecular Assembly of Gold Nanoparticles and Cucurbituril

Abstract: Gold nanoparticles ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
127
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(134 citation statements)
references
References 38 publications
4
127
1
2
Order By: Relevance
“…Therefore, CB[n] macrocycles can be used to stabilize the metal nanoparticles. Corma and co-workers have shown that the size of metal nanoparticles can be controlled by encapsulation in CB [7], which shows unprecedented behavior at stabilizing very small gold nanoparticles [57]. TEM images of gold nanoparticles obtained in the presence and absence of CB are shown in Fig.…”
Section: Hostmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, CB[n] macrocycles can be used to stabilize the metal nanoparticles. Corma and co-workers have shown that the size of metal nanoparticles can be controlled by encapsulation in CB [7], which shows unprecedented behavior at stabilizing very small gold nanoparticles [57]. TEM images of gold nanoparticles obtained in the presence and absence of CB are shown in Fig.…”
Section: Hostmentioning
confidence: 98%
“…9. TEM images of gold nanoparticles obtained in the absence of CB (top, left) and in the presence of CB [5] (top, right), CB [6] (bottom, left), and CB [7] (bottom, right) [57].…”
Section: Hostmentioning
confidence: 99%
“…A family of cucurbit[n]uril, CB [n], hosts comprising of methylene-bridged glycouril units have attracted considerable attention owing to their potential applications in organic synthesis [1][2][3][4], molecular recognition [5,6], nanoscience [7,8], catalysis [9][10][11], drug delivery vehicles [12] and separation technology [13,14]. The number of glycouril units in cucucrbituril homologues renders varying size to their hydrophobic cavity while portal carbonyl groups on portals provide hydrophilic exterior to these macrocycles.…”
Section: Introductionmentioning
confidence: 99%
“…8,12,13 Cucurbituril cavities are hydrophobic and can accommodate many guest molecules in a series of inclusion compounds, just like cyclodextrins and calixarenes (see molecular structure in Figure 1). 11 Corma et al 14 have recently synthetized gold nanoparticles using CB cavities as templates, obtaining almost monodisperse particle populations, a very important aspect when one aims at absolute size control. The size control in this level is even more important during the production of quantum dots, since their physical and physicochemical properties are strongly size-and shapedependent.…”
Section: Introductionmentioning
confidence: 99%